Absence of translationally selected synonymous codon usage bias in Helicobacter pylori - Lafay, Benedicte; Atherton, John C; Sharp, Paul M (Microbiology (Society for General Microbiology), 2000)
Institute of Genetics 1 , and Division of Gastroenterology, Department of Medicine and Institute of Infections and Immunity 2 , University of Nottingham, Queens Medical Centre, Nottingham NG7 2UH, UK Author for correspondence: Paul M. Sharp. Tel: +44 115 970 9263. Fax: +44 115 970 9906. e-mail: paulatevol.nott.ac.uk Synonymous codon usage in the complete genome of Helicobacter pylori was investigated. The moderate A+T-richness of the genome (G+C=39 mol%) is reflected in the overall synonymous codon usage but the frequencies of some codons cannot be explained by simple mutational biases. A low level of heterogeneity among genes was observed, but this does not appear to be due to varying mutational bias or translational selection. Some of the heterogeneity was due to amino acid composition variation among the encoded proteins, and some may be attributable to recent acquisition of genes from other species. Since Hel. pylori codon usage is not dominated by biased mutation patterns, the absence of evidence for translationally mediated selection among synonymous codons is striking. This has implications with regard to the life history of this species, and in particular suggests that Hel. pylori strains are not subject to periods of competitive exponential growth. Despite the lack of selected codon usage, base composition immediately after the translation initiation site is skewed, consistent with selection against secondary structure formation in this region. Keywords: codon usage, Helicobacter pylori , translational selection, cag pathogenicity island, molecular evolution Abbreviations: GC3 s , G+C content at synonymously variable third positions of sense codons; N c , effective number of codons; RSCU, relative synonymous codon usage a Present address: Centre dOcéanologie de Marseille, CNRS-UMR 6540, Station Marine dEndoume, rue Batterie des Lions, 13007 Marseille, France.